2019
DOI: 10.2147/ndt.s183632
|View full text |Cite
|
Sign up to set email alerts
|

<p>Hyperbaric oxygen therapy attenuates neuronal apoptosis induced by traumatic brain injury via Akt/GSK3&beta;/&beta;-catenin pathway</p>

Abstract: BackgroundGiven that the therapeutic effect of hyperbaric oxygen (HBO) therapy on traumatic brain injury (TBI) has been debated for a long time, it is necessary to clarify the mechanism underlying the effect of HBO on acute TBI.MethodsThis study investigated the effect of HBO therapy on neuronal apoptosis induced by acute TBI using the mouse model of TBI. The number of apoptotic cells and expression of apoptosis-associated factors (including caspase 3, pAkt/Akt, pGSK3β/GSK3β, and β-catenin) in pericontusional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Strong evidence has demonstrated that GSK‐3β activation is involved in the excitotoxicity process of memory dysfunction in neurodegenerative diseases . The GSK‐3β/β‐catenin signal pathway is crucial for neuronal apoptosis, and its activation accelerates hippocampal neuroapoptosis by targeting proteins related to apoptosis or interacting with other signal pathways . In this study, significantly activated GSK‐3β was identified in the hippocampus of rats given SEV, which was consistent with other studies.…”
Section: Discussionsupporting
confidence: 91%
“…Strong evidence has demonstrated that GSK‐3β activation is involved in the excitotoxicity process of memory dysfunction in neurodegenerative diseases . The GSK‐3β/β‐catenin signal pathway is crucial for neuronal apoptosis, and its activation accelerates hippocampal neuroapoptosis by targeting proteins related to apoptosis or interacting with other signal pathways . In this study, significantly activated GSK‐3β was identified in the hippocampus of rats given SEV, which was consistent with other studies.…”
Section: Discussionsupporting
confidence: 91%
“…Many studies have explored the potential effects of several medical gases on nerve regeneration, oxidative stress and apoptosis after TBI. Hyperbaric oxygen promotes nerve regeneration and attenuates apoptosis in animal models of TBI and patients . Hydrogen sulphide offered neuroprotection after TBI in mice, together with reduced apoptosis and oxidative stress .…”
Section: Discussionmentioning
confidence: 99%
“…Mice in which TBI was induced were placed in a hyperbaric chamber for 90 min. This regimen reduced the number of apoptotic neurons, as well as the mRNA expression of caspase-3 and the level of cleaved-caspase-3 ( He et al, 2019 ). These effects were associated to an increased expression of β-catenin and decreased expression of GSK3β ( He et al, 2019 ).…”
Section: The Wnt Pathway In Tbimentioning
confidence: 99%